(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
This study aims to stand at some of the Maghreb liberation struggle stations between Tunisia and morocco , after the end of the second world war , where the movements of independence in the Maghreb countries marked a major change in the method of liberation struggle , beginning with establishment of the Arab Maghreb office in Cairo in 1947 , which formed a prominent station for Maghreb work through its contribution to the definition the Moroccan issue , especially in the Arab orient , to hold the leaders of the national liberation movements in the three Maghreb countries . (Tunisia- Algeria-Morocco) the tangier conference of 1958, which came as an addition to the consolidation of the efforts for the struggle for the complete liberation and independence of the countries of the Maghreb. Key words: Maghreb joint struggle- Maghreb liberation struggle- Maghreb conference - Arab Maghreb office in Cairo